(3JUQja GdRfLGfjs - (3GdNRQLj GdnqRrfLGfj, GdYRj (B((3YR GdOjf(B)(3, YHO GdhgGH Hf EHQGgje Hf YHO GdhgGH, J (B655 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3GYde Cf GdJUQja aj GddZI GdJZjQ haj GdUfGYI GdJMhjd GdCUd GdhGMO Edi CeKdI eNJdaI deYGf ebUhOI dG JMUd EdG HgG Ke GdaYd EeG KdGKj hEeG QHGYj hcd hGMO efgeG EeG eLQO Ch eRjO (B...s
(3BNQgG (B:s
.. (3EdG eG ajg JGA GdJCfjK efgeG aGdhUa HGdhGMOI hPdc fMh QMeJg QMeI hGMOI hOMQLJg OMQLI hGMOI hGdaYdI HGdcSQ ddfhY ef GdaYd Jbhd Nh MSf GdWYeI hGdLdSI (B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4\179s
(3cTa GdXfhf (B1\412s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdUQas